The mirror within the mirror: Reflections on multiculturalism, theory and practice. - Catherine A. Hansman; Sherwood E. Smith (Adult Education Research Conference, 1997)
The purpose of this paper is to explore the ways in which adult education graduate students' perceptions of race, class, gender and sexual orientation were transformed by the end of graduate adult education courses which included readings, reflection, discussions and other activities designed to foster self-awareness, critical reflection and cultural sensitivity.